Pengembangan Sistem Pemantauan Kebakaran Real-Time dan Peringatan Dini Menggunakan Teknologi LoRa pada Kawasan Perkotaan - Abdul Rahman; Eka Puji Widiyanto (LPPM Institut Pendidikan Nusantara Global, 2025)
Fires in urban areas require reliable monitoring and early warning systems to reduce potential losses. This study aims to evaluate the performance of components that build an urban fire monitoring and early warning system, consisting of the DHT22 temperature and humidity sensor, MQ-2 smoke sensor, 5-channel IR flame detector, and LoRa E220-900T22D communication module as the main components of the IoT-based system. The testing methods include measuring the accuracy of temperature and humidity using the DHT22, smoke detection tests with MQ-2, fire detection distance tests with the IR flame detector, and communication range tests of LoRa in urban environments. The results show that the DHT22 provides high accuracy with an average of 98.67% for humidity and 97.82% for temperature. The MQ-2 consistently detects varying smoke concentrations, while the IR flame detector perfectly detects fire at a distance of 90 cm on all channels and only on certain channels at 300 cm. The LoRa module demonstrates an effective range of 1–2 km with relatively high reliability, though performance decreases beyond 3 km due to physical obstacles and signal interference. Overall, the system can be effectively implemented for urban fire monitoring and early warning, although additional strategies such as denser gateway placement or mesh architecture are required to improve communication stability.